Numerical Study of The Airfoil Pitch Angle on The Darrieus-Savonius Combination Turbine - Erifive Pranatal; Renanda Bayu Harsi (Institut Teknologi Adhi Tama Surabaya, 2021)
AbstractThe Darrieus turbine is used as an ocean current converter to generate renewable electrical energy. One way to improve turbine performance is to determine the optimal pitch angle. Therefore, the purpose of this study was to determine the optimal pitch angle of the NACA 0018 airfoil with angle variations of -6°, -2°, 0° and 2°. Numerical method with the help of Ansy Fluent software was carried out for the construction of the turbine. The result of this research is that the angle of 2° produces the largest coefficient of power and torque compared to other angles. This happens because the direction of the lifting force on the forward airfoil is in accordance with the rotation of the turbine.Keywords: Ocean Current, Turbine, Pitch Angle